2003
DOI: 10.1202/375.1
|View full text |Cite
|
Sign up to set email alerts
|

An Occupational Exposure Assessment of a Perfluorooctanesulfonyl Fluoride Production Site: Biomonitoring

Abstract: This investigation randomly sampled a fluorochemical manufacturing employee population to determine the distribution of serum fluorochemical levels according to employees' jobs and work areas. Previous analyses of medical surveillance data have not shown significant associations between fluorochemical production employees' clinical chemistry and hematology tests and their serum PFOS and perfluorooctanoate (PFOA, C(7)F(15)COO(-)) concentrations, but may have been subject to nonparticipation bias. A random sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 0 publications
1
76
0
1
Order By: Relevance
“…PFOS has been detected at low parts per billion (nanogram per milliliter) concentrations in the general population (3M Company 2003;Hansen et al 2001;Olsen et al 2003b), although the scope and sample size of these investigations have been limited. Serum PFOS concentrations among production employees working in POSF-related processes have averaged between 0.5 and 2 ppm depending on work activity (range < 0.1-12 ppm) (Olsen et al 1999(Olsen et al , 2003a(Olsen et al , 2003c. A large body of toxicology and epidemiology data is available for review regarding PFOS [3M Company 2003; Organisation for Economic Co-operation and Development (OECD) 2002].…”
Section: Research | Articlementioning
confidence: 99%
“…PFOS has been detected at low parts per billion (nanogram per milliliter) concentrations in the general population (3M Company 2003;Hansen et al 2001;Olsen et al 2003b), although the scope and sample size of these investigations have been limited. Serum PFOS concentrations among production employees working in POSF-related processes have averaged between 0.5 and 2 ppm depending on work activity (range < 0.1-12 ppm) (Olsen et al 1999(Olsen et al , 2003a(Olsen et al , 2003c. A large body of toxicology and epidemiology data is available for review regarding PFOS [3M Company 2003; Organisation for Economic Co-operation and Development (OECD) 2002].…”
Section: Research | Articlementioning
confidence: 99%
“…On the other hand, there is a report that workers in a fluorochemical manufacturing plant were exposed to PFCs. Geometric means of serum concentrations of PFOA and PFOS were 941 µg/L and 899 µg/L respectively 16) . It has recently been suggested that PFOS and related compounds are human and animal carcinogens [17][18][19] .…”
mentioning
confidence: 99%
“…Little information is available on the intake, metabolism and elimination of PFOA in humans. Studies in occupational medicine carried out at 3M showed plasma concentrations of PFOA in a range of 0.04 to 12.7 mg/L, but no significant influence on the haematological, hepatic, hormonal or urinary parameters was found [3,4]. The biological half-life of PFOA is considerably higher in humans than in laboratory animals.…”
Section: Perfluorooctanoic Acidmentioning
confidence: 97%
“…APFO dissociates in water to form PFOA. The main global producer of PFOA was the 3M company, which announced discontinuation of the production of PFOA and its salts in May 2000 on account of their toxicity in animal studies and their persistence in the environment [3]. Neither photolytic nor biological decomposition takes place in the environment due to the high stability of the C-F bond [2].…”
Section: Perfluorooctanoic Acidmentioning
confidence: 99%